Hubungan Kualitas Produk dan Citra Merek dengan Keputusan Pembelian pada Brand Fashion Lokal - Jaya Kusuma; Halimah Zahrah (Indo Publishing, 2026)
The local fashion industry faces increasingly intense competition driven by changes in young consumers’ lifestyles. Screamous, a Bandung-based streetwear brand, has experienced declining market share and sales, indicating weakened purchase decisions. This study aims to analyze the effects of product quality and brand image on consumers’ purchase decisions toward Screamous. A quantitative causal approach was applied using a survey of 100 followers of the Instagram account @jayaaksmaa. The results show that product quality and brand image have positive and significant effects, both partially and simultaneously, on purchase decisions. The study concludes that strengthening product quality and brand image is essential to enhance competitiveness and contributes to the marketing literature on local fashion brands.